Maneuvers : the international politics of militarizing women's lives - Enloe, Cynthia H., 1938- (University of California Press, 2000)
Enloe outlines the dilemmas feminists around the globe face in trying to craft theories and strategies that support militerized women, locally and internationally, without unwittingly being militerized themselves.